Caryopteris alternifolia (Ajugoideae, Lamiaceae), a distinct new species from Guangdong, China - Chen, You-Sheng; Xiang, Chun-Lei; Xu, Lian-Sheng; Jin, Zi-Caho (Phytotaxa, 2020)
Caryopteris alternifolia (Ajugoideae, Lamiaceae), a new species from eastern Guangdong, China, is described based on morphological and molecular phylogenetic data. Both molecular and morphological evidence indicates that C. alternifolia is closely related to C. incana, but it is easily distinguished from the latter by its leaves alternate, mostly entire, 1–3 cm long, 0.15–0.4 cm wide and sessile, and cymes with 5 flowers (vs. leaves opposite, dentate, 3–4.5 cm long, 0.4–0.8 cm wide and with petioles 0.3–1.7 mm long, and cymes with more than 10 flowers).